2003
DOI: 10.1007/s10038-003-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the MTHFR 1298A→C and 677C→T polymorphisms as risk factors for neural tube defects

Abstract: The thermolabile variant (677TT) of methylenetetrahydrofolate reductase (MTHFR) is a known risk factor for neural tube defects (NTDs). The relationship between a second MTHFR polymorphism (1298A fi C) and NTD risk has been inconsistent between studies. We genotyped 276 complete NTD triads (mother, father and child affected with an NTD) and 256 controls for MTHFR 1298A fi C. Our findings do not support a role for the 1298A fi C polymorphism in NTDs (OR 0.85 (95% CI 0.49-1.47), p= 0.55), nor do we observe a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 19 publications
5
40
0
9
Order By: Relevance
“…However, this linkage disequilibrium is not complete, since the presence of some individuals with the haplotype T-C was observed in some studies (Shi et al, 2003;Parle-McDermott et al, 2003;Scala et al, 2006). In our study, in a total sample of 266 women, only one with this haplotype was observed, confirming its negative selection.…”
Section: Discussionsupporting
confidence: 59%
“…However, this linkage disequilibrium is not complete, since the presence of some individuals with the haplotype T-C was observed in some studies (Shi et al, 2003;Parle-McDermott et al, 2003;Scala et al, 2006). In our study, in a total sample of 266 women, only one with this haplotype was observed, confirming its negative selection.…”
Section: Discussionsupporting
confidence: 59%
“…The identification of polymorphisms within MTHFR was motivated by the known association between the A222V (677C->T) polymorphism and NTDs in many populations. Furthermore, the identification of a second common polymorphism E429A (1298C->A), in linkage disequilibrium with A222V, has been shown to have NTD association risk in some [van der Put et al, 1998;Richter et al, 2001;De Marco et al, 2002] but not all populations [Parle-McDermott et al, 2003]. Despite the enormous focus on MTHFR, NTD studies and other disease associations have been generally restricted to examining the effect of the presence of one or both of these two common polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…In NTD families in Italy and Turkey, the MTHFRA1298C polymorphism was found to be a genetic determinant for NTD risk www.intechopen.com (Boduroğlu et al, 2005;De Marco et al, 2002) but there are conflicting studies in spina bifida occulta patients in Turkey . Other studies have failed to find an association between the 1298A-C polymorphism and risk of NTDs (Parle-McDermott et al, 2003).…”
Section: A1298cmentioning
confidence: 92%